Flash-X: A multiphysics simulation software instrument - Anshu Dubey; Klaus Weide; Jared O’Neal; Akash Dhruv; Sean Couch; J. Austin Harris; Tom Klosterman; Rajeev Jain; Johann Rudi; Bronson Messer; Michael Pajkos; Jared Carlson; et al. (SoftwareX, 2022)
Flash-X is a highly composable multiphysics software system that can be used to simulate physical phenomena in several scientific domains. It derives some of its solvers from FLASH, which was first released in 2000. Flash-X has a new framework that relies on abstractions and asynchronous communications for performance portability across a range of increasingly heterogeneous hardware platforms. Flash-X is meant primarily for solving Eulerian formulations of applications with compressible and/or incompressible reactive flows. It also has a built-in, versatile Lagrangian framework that can be used in many different ways, including implementing tracers, particle-in-cell simulations, and immersed boundary methods.